Community-acquired and healthcare-associated Staphylococcus aureus infections in a pediatric hospital in southern Brazil over 8 years: how common is MRSA? - Fassbind, Derrick Alexandre; Rezende, Raíssa Queiroz; Dias, Cícero Armídio Gomes; Motta, Fabrizio (Frontiers in Pediatrics, 2023)
Backgrounds Both healthcare-associated and community-acquired methicillin-resistant Staphylococcus aureus (MRSA) infections are relevant in children. The objective of our study was to evaluate their impact in a pediatric hospital in southern Brazil. Methods Data from patients under 18 years of age with S. aureus infections between January 2013 and December 2020 were retrospectively analyzed. Data were collected regarding infection site, infection type (community-acquired or healthcare-associated), susceptibility to oxacillin [methicillin-susceptible S. aureus (MSSA) or MRSA] and other antimicrobials. We analyzed the evolution of the susceptibility rates for the isolates over this period. Results A total of 563 patients were included, among whom the prevalences of community- and hospital-acquired MRSA infections were 46.1% and 8.1%, respectively. No significant change occurred in these prevalences over the study period. In community-acquired infections, MSSA was significantly more associated with osteoarticular infections and MRSA was more associated with respiratory and intra-abdominal infections. In healthcare-associated infections, there was an association between MSSA and primary bloodstream infections and between MRSA, skin/soft tissue infections, and respiratory infections. Community-acquired MRSA were highly susceptible to trimethoprim-sulfamethoxazole (96.1%), clindamycin (88.4%), and doxycycline (99.0%). Conclusion Our study draws attention to the high rates of MRSA in community-acquired staphylococcal infections in this population, indicating a need to review initial protocols for severe staphylococcal infections according to local epidemiology.